THE MODERN PROBLEMS OF PERSONNEL TRAINING WHILE ESTABLISHING THE SPECIAL PHARMACEUTICAL HIV-PATIENTS’ HELPING SYSTEM - Петров, Андрей Георгиевич; Хорошилова, Ольга Владимировна; Семенихин, Виктор Андреевич; Филимонов, Сергей Николаевич; Черных, Наталья Степановна; Вакулова, Тамара Михайловна (Medicine in Kuzbass, 2023)
Lately there have been a lot of investigations which aimed at the establishment of the concept of pharmaceutical help for treatment of various diseases, e.g. of HIV. According to the data given by Russian consumer supervision, HIV still remains one of the most widespread diseases. At the same time it lacks the training of pharmaceutical personnel specializing in «Clinical pharmacy», which is essential for medical treatment of HIV-patients. The article gives reasons for the necessity of optimizing this personnel training direction.
Keywords: HIV and AIDS; pharmaceutical education; personnel training